Planeación Estrátegica De La Cooperativa De Ahorro Y Crédito De La Pequeña Y Mediana Empresa Ciudadana De Macará (Coopymec), Socia De La Red De Entidades Financieras Equitativas (Refse) De La Región Siete” - Lapo Garrido, Karen Lourdes (2016)
This research paper entitled “Strategic Planning COOPERATIVE SAVINGS AND CREDIT OF SMALL AND MEDIUM ENTERPRISES MACARÁ CITIZEN (COOPYMEC) PARTNER NETWORK EQUITABLE FINANCIAL INSTITUTIONS (REFSE) REGION OF SEVEN “. The starting point was the determination of the objectives of the study, being the following ; conduct a strategic planning overall objective and within the specific objectives for an economic financial diagnosis and determine the mission, vision , objectives, strategies , activities and budget the cooperative , the same that marked the path of the procedures , actions and analysis of this work. The heart of the work involved in conducting the external analysis which came to obtain the information necessary to compile the EFE matrix (matrix evaluation of external factors), as well as conducting competitive profile matrix MPC. We proceeded to perform the analysis of the internal factors , for this survey was applied to both internal stakeholders and external and financial analysis with the application of vertical and horizontal financial analysis , implementation of financial indicators , the information obtained served as the basis for developing EFI matrix ( matrix evaluation of internal factors). With the information obtained through the completion of the analysis of factors both external and internal , we proceeded to the development of the SWOT matrix , and technical conjugation of FO crosses - FA - DO - DA , they came to get strategies to that entity , so also to determine the position of the profile of strategies for cooperative matrix strategic position and action evaluation SPACE was applied and resulted in the quantitative strategic planning matrix by MPEC which allowed classify, identify and select strategies in order for the entity. The structure of the strategic objectives is qualified by determining Strategy, Tactics, Politics, Lines of Action, Resources, Time, and Responsible for compliance, Expected Results, Financing, Development and Budget. In the second half of this thesis, the conclusions are stated with the same respective recommendations that generate an important contribution of this work.